Outcomes of Spironolactone Withdrawal in Dilated Cardiomyopathy With Improved Ejection Fraction - Chen, Yanjia; Qiu, Zeping; Jiang, Jie; Su, Xiuxiu; Huang, Fanyi; Tang, Jing; Jin, Wei (Frontiers in Cardiovascular Medicine, 2021)
Background The feasibility of spironolactone withdrawal in dilated cardiomyopathy patients with improved ejection fraction remains unknown. This study sought to determine whether spironolactone can be withdrawn safely in this circumstance. Methods Consecutive patients with idiopathic dilated cardiomyopathy and prescribed spironolactone at discharge were included in this prospective, observational cohort using the Risk Evaluation and Management in Heart Failure Trial (NCT02998788) database. Those patients who experienced an absolute left ventricular ejection fraction (LVEF) improvement≥10% and a second measurement of LVEF>40% would choose whether to continue spironolactone therapy and be included in final analysis. The primary endpoint was dilated cardiomyopathy relapse within 12 months, defined as a more than 10% reduction in LVEF, a 15% or greater increase in LVESVi, a two-fold rise in NT-proBNP or clinical signs of heart failure. Results Seventy patients achieved an ejection fraction improvement and were included in the final analysis, of whom 30 chose to continue spironolactone and 40 decided to withdraw. In primary endpoint analysis, 23 (58%) patients from the withdrawal group and 4 (13%) patients from the continuation group relapsed (relative risk for relapse: 4.31; 95% confidence interval: 1.67 to 11.11; P<0.001). Patients from the withdrawal group experienced more symptoms aggravation than the continuation group. No secondary safety endpoint was recorded. Improvements in cardiac structure parameters were no longer observed after spironolactone withdrawal, while improvements persisted in continuation group. Conclusions Most dilated cardiomyopathy patients with improved ejection fraction will relapse following spironolactone withdrawal. These results should be weighed before spironolactone withdrawal was attempted.